Fragmentation-Rearrangement of Peptide Backbones Mediated by the Air Pollutant NO2 - Gamon, Luke F.; Nathanael, Joses G.; Taggert, Bethany I.; Henry, Fraser A.; Bogena, Jana; Wille, Uta (Chemistry : a European journal, 2015)
The fragmentation–rearrangement of peptide backbones mediated by nitrogen dioxide, NO2., was explored using di‐, tri‐, and tetrapeptides 8–18 as model systems. The reaction, which is initiated through nonradical N‐nitrosation of the peptide bond, shortens the peptide chain by the expulsion of one amino acid moiety with simultaneous fusion of the remaining molecular termini through formation of a new peptide bond. The relative rate of the fragmentation–rearrangement depends on the nature of the amino acids and decreases with increasing steric bulk at the α carbon in the order Gly>Ala>Val. Peptides that possessed consecutive aromatic side chains only gave products that resulted from nitrosation of the sterically less congested N‐terminal amide. Such backbone fragmentation–rearrangement occurs under physiologically relevant conditions and could be an important reaction pathway for peptides, in which sections without readily oxidizable side chains are exposed to the air pollutant NO2.. In addition to NO2.‐induced radical oxidation processes, this outcome shows that ionic reaction pathways, in particular nitrosation, should be factored in when assessing NO2. reactivity in biological systems. NO2. mediates the fragmentation– rearrangement of peptide backbones, which leads to shortening of the peptide chain by expulsion (see scheme) of one amino acid moiety with simultaneous fusion of the remaining ends through formation of a new peptide bond.